Pengembangan Media Game Edukasi untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran IPA Kelas IV - Mufidah, Eli; Lestari, Putri Dwi (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2022)
This study aims to develop learning media for android-based educational games in science subjects for energy sources, so as to increase the activity of students and increase their understanding of various energy sources and their uses. This type of research is research and development (R&D), which refers to the ADDIE development model (Analysis, Design, Development, Implement, and Evaluation). The data obtained will be analyzed with descriptive quantitative and qualitative data. The feasibility of learning media for Android-based educational games from the research results is